2022
DOI: 10.2169/internalmedicine.8076-21
|View full text |Cite
|
Sign up to set email alerts
|

Lustrous White Erosions Surrounded by an Erythematous Mucosa: A Novel Endoscopic Finding of Gastric Lesions in Patients with Wilson Disease

Abstract: Wilson disease is an inherited copper metabolism disorder. We herein report a novel endoscopic finding in three men with Wilson disease. These patients underwent upper endoscopy due to gastrointestinal symptoms or during follow-up. In each case, endoscopy revealed lustrous white erosions surrounded by an erythematous mucosa in the greater curvature of the gastric body. A biopsy of the lesions showed orcein-positive tissue, indicating copper deposition, in the interstitial stroma and fundic glands of the mucosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In addition, gastric mucosal injury has recently been reported to be associated with zinc acetate dihydrate tablet intake. Kitagawa et al reported that in three cases of Wilson's disease treated with zinc acetate, lustrous white erosions surrounded by erythematous mucosa were observed in the greater curvature of the gastric corpus [ 8 ]. We retrospectively analyzed 47 patients who underwent upper gastrointestinal endoscopy while taking oral zinc acetate dihydrate [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, gastric mucosal injury has recently been reported to be associated with zinc acetate dihydrate tablet intake. Kitagawa et al reported that in three cases of Wilson's disease treated with zinc acetate, lustrous white erosions surrounded by erythematous mucosa were observed in the greater curvature of the gastric corpus [ 8 ]. We retrospectively analyzed 47 patients who underwent upper gastrointestinal endoscopy while taking oral zinc acetate dihydrate [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of zinc acetate dihydrate-associated gastric lesions has not yet been elucidated. Kitagawa et al reported that orcein-positive granules were observed in the fundic glands and interstitium of the stomach in three cases of Wilson's disease, suggesting cytotoxicity induced by copper deposition [ 8 ]. Although we performed energy-dispersive X-ray analysis of the biopsy specimen from another patient with hypozincemia, no copper or zinc was detected [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation